EVALUASI PELAKSANAAN ELEKTRONIC MEDICAL RECORD (EMR) DI RAWAT JALAN RSU QUEEN LATIFA YOGYAKARTA: EVALUASI PELAKSANAAN ELEKTRONIC MEDICAL RECORD (EMR) DI RAWAT JALAN RSU QUEEN LATIFA YOGYAKARTA - Nasiatul Aisyah Salim; Ulfah Rizqie Miftah Hani; Dewi Ariyani Wulandari (Jurnal Infokes, 2022)
Elektronic Medical Records have been widely applied in Asian countries including Indonesia. Queen Latifa General Hospital Yogyakarta has implemented EMR on an outpatient basis since July 2019. In practice, there are still obstacles in implementation. So it is necessary to evaluate by looking at the satisfaction of service users, usefulness, ease of use, quality of information, performance expectations and attitudes of officers. The hope is that there will be improvements, helping performance and learning about the development of management systems in hospitals. The purpose of the study was to evaluate the implementation of electronic medical records in outpatient services at Queen Latifa General Hospital Yogyakarta. This research is quantitative with cross sectional design. The population is an outpatient staff. The sample is 81 people with total sampling technique. Data collection using questionnaires totaling 33 questions and open interviews. Data analysis with univariate analysis. The results showed that service user satisfaction was 97,5 % good, usefulness was 95,1 % good, user convenience was 95,1 % good, information quality was 87,7 % good, performance expectations were 87,7 % good, and the attitude of the officers was 95,1 % good. The conclusion that the implementation of electronic medical records in outpatient Queen Latifa Hospital Yogyakarta is in the good category for all variables. It is recommended that further researchers use other variables such as facilities, security, timeliness.